2016
DOI: 10.1111/imj.13224
|View full text |Cite
|
Sign up to set email alerts
|

Clinical trials of medicinal cannabis for appetite‐related symptoms from advanced cancer: a survey of preferences, attitudes and beliefs among patients willing to consider participation

Abstract: Justification of modes other than tablets/capsules and variable understanding about cannabis and trials will need addressing in trial-related information to optimise recruitment and ensure that consent is properly informed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
53
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(58 citation statements)
references
References 26 publications
4
53
0
1
Order By: Relevance
“…Those rates are lower than the rates in a multinational Internet-based survey of medicinal cannabis users conducted by Hazekamp et al 10 , who found that 95% and 69% had tried inhaled and oral administration respectively. Interestingly, when planning future clinical trials, patients might prefer oral administration of cannabis, as was shown by Luckett et al 14 in a 2016 study.…”
Section: Discussionmentioning
confidence: 94%
“…Those rates are lower than the rates in a multinational Internet-based survey of medicinal cannabis users conducted by Hazekamp et al 10 , who found that 95% and 69% had tried inhaled and oral administration respectively. Interestingly, when planning future clinical trials, patients might prefer oral administration of cannabis, as was shown by Luckett et al 14 in a 2016 study.…”
Section: Discussionmentioning
confidence: 94%
“…Comparing our results with the results for other cancer populations is difficult because of the limited number of studies. An Australian study evaluating cannabis use among patients with advanced cancer and/or a poor appetite at cancer and palliative care clinics found that 26 of 204 patients (13%) had previously used medical cannabis . A study from Israel, where medical cannabis is legal, estimated that only 1.7% of 17,000 cancer patients had acquired a permit for medical marijuana .…”
Section: Discussionmentioning
confidence: 99%
“…An Australian study evaluating cannabis use among patients with advanced cancer and/or a poor appetite at cancer and palliative care clinics found that 26 of 204 patients (13%) had previously used medical cannabis. 27 A study from Israel, where medical cannabis is legal, estimated that only 1.7% of 17,000 cancer patients had acquired a permit for medical marijuana. 28 Among Interest in learning about cannabis during cancer therapy stratified by age (*P .05, **P < .01, and ***P < .001).…”
Section: Discussionmentioning
confidence: 99%
“…3 However, the uptake of prescribed medical cannabis has been limited amid caution from medical professional groups. 4,5 Community support for prescribed medical cannabis continues to grow, 6 possibly influenced by media reporting; surveys of patients with chronic pain, 7 cancer, 8 and epilepsy 9 have found that considerable numbers of Australians have either used (10e20%) or would consider using cannabis products for therapeutic purposes. However, knowledge of the unregulated use of medical cannabis in Australian remains imprecise because it is generally illegal.…”
mentioning
confidence: 99%